Bouchardia rosea, a vanishing brachiopod species of the Brazilian platform: taphonomy, historical ecology and conservation paleobiology - Simoes, M. G. [UNESP]; Rodrigues, S. C.; Kowalewski, M. (Taylor & Francis Ltd, 2009)
Dead-live faunal comparisons can offer powerful data to detect natural or human-induced population changes in the late Holocene. Here, we document dead-live comparisons for death assemblages of the brachiopod Bouchardia rosea in nearshore (0-45m) environments along the northern coast of São Paulo State, Brazil. The sampling programme included 30 stations (14 at Ubatuba, 16 at Picinguaba bay). The bottom was sampled via Van Veen grab sampler, and also dredged. Out of 30 stations, 22 yielded brachiopods. The fidelity estimates were obtained by direct comparisons of live biota with dead shells. A total of 6627 brachiopods were recovered, 5339 (80.6%) from Ubatuba and 1288 (19.4%) from Picinguaba. Out of these, 6621 (99.9%) were empty, dead shells, while only six individuals (0.1%) were found alive, all in the Picinguaba Bay. These results suggest extremely poor dead-live compositional fidelity for B. rosea assemblages. The spatial data suggest that the distribution of B. rosea accumulations has been highly patchy in the region, whereas the great scarcity of live brachiopods may point to a recent decline in local populations. Several lines of evidences indicate that changes in water temperature, nutrient availability, population history and even pollution, may have all affected spatio-temporal dynamics of B. rosea populations.
Keywords: fidelity; taphonomy; paleoecology; brachiopods; South Atlantic Ocean; late Holocene